Methodological Challenges in the Study of Emotions in Politics and How to Deal With Them. Issue 6 (30th October 2019) - Lynggaard, Kennet
Abstract : This introductory article to the special issue zooms in on the literature on political emotions with a specific focus on methodological questions of "how to study" political emotions. To the extent that methodological matters are addressed in the extant literature, the associated challenges are often portrayed as a clash between social science and natural science disciplines, a clash frequently illustrated by the meeting between political science and neuroscience. Rather than being a clash between academic disciplines, this article argues that many of the methodological challenges facing emotional research have their origin in scholars' diverse views on the relationship between themselves as researchers and political emotions as a research object. In the light of this acknowledgment, the article encircles and discusses the methodological challenges associated with three key conceptual distinctions between: (1) individual and collective emotions, (2) emotions and reason, and between (3) involuntary political emotions and the strategic usage of political emotions. Using the contributions to this special issue as illustrations, the article argues in favor of moving beyond mutually exclusive dichotomies regarding these conceptual distinctions and offers pathways for dealing with current methodological challenges to emotional research. It points to methodological pluralism, transparency, and context‐sensitive research strategies.